Hazard Analysis Critical Control Point (HACCP) sebagai jaminan keamanan produk Sarang Burung Walet Tujuan Ekspor ke Tiongkok - Rizal Eko Kurniawan; Chaerul Basri; Hadri Latif (Acta VETERINARIA Indonesiana, 2021)
ABSTRACT Edible Bird Nest (EBN) is a food product of animal origin that obtains many benefits for Indonesia's export commodities. EBN contains many nutrients in which it is widely utilized in the health sector. EBN products have been exported to various countries and one of them is China. EBN products exported to China have potential harms such as physical, biological, and chemical hazards that pose risks to human health. Therefore, every product of animal origin needs food safety assurance. Hazard Analysis Critical Control Point (HACCP) is a food safety system developed to identify, evaluate, and control food safety hazards. HACCP is a system developed to prevent or reduce hazards to an acceptable extent during the globally adopted production. Through the implementation of a food safety assurance system in the EBN, it is expected to lower the risk of food hazards. This paper discussed HACCP in ensuring food safety of animal origin, especially Edible Bird Nest to fulfill the export requirements of Edible Bird Nest to China. Keywords: Animal-origin Food Safety, HACCP, Edible Bird Nest